2012
DOI: 10.2119/molmed.2012.00088
|View full text |Cite
|
Sign up to set email alerts
|

Flurbiprofen, a Cyclooxygenase Inhibitor, Protects Mice from Hepatic Ischemia/Reperfusion Injury by Inhibiting GSK-3β Signaling and Mitochondrial Permeability Transition

Abstract: Flurbiprofen acts as a nonselective inhibitor for cyclooxygenases (COX-1 and COX-2), but its impact on hepatic ischemia/ reperfusion (I/R) injury remains unclear. Mice were randomized into sham, I/R and flurbiprofen (Flurb) groups. The hepatic artery and portal vein to the left and median liver lobes were occluded for 90 min and unclamped for reperfusion to establish a model of segmental (70%) warm hepatic ischemia. Pretreatment of animals with flurbiprofen prior to I/R insult significantly decreased serum ala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 34 publications
4
16
0
Order By: Relevance
“…However, there is no direct evidence that H 2 S has an effect on systemic dynamics. Our study confirmed that intravenous injection of 25 μmol/kg NaHS had no effect on systemic hemodynamics at various time points in a rat model of 70% warm hepatic I/R, which is widely used in studies focused on hepatic I/R [25,28,44,45,46,47]. Given that the hepatic portal system was not completely blocked (with the blood supply maintained in the right lobe and the caudate lobe), the blood returns from the postcava to the right atrium unaffected.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…However, there is no direct evidence that H 2 S has an effect on systemic dynamics. Our study confirmed that intravenous injection of 25 μmol/kg NaHS had no effect on systemic hemodynamics at various time points in a rat model of 70% warm hepatic I/R, which is widely used in studies focused on hepatic I/R [25,28,44,45,46,47]. Given that the hepatic portal system was not completely blocked (with the blood supply maintained in the right lobe and the caudate lobe), the blood returns from the postcava to the right atrium unaffected.…”
Section: Discussionsupporting
confidence: 76%
“…Mitochondria were isolated by gradient centrifugation as we previously described [25]. Briefly, fresh liver tissues (1 g) were homogenized with 8 ml of isolation buffer containing 220 mmol/L D-mannitol, 70 mmol/L sucrose, 10 mmol/L Tris-HCl, 1 mmol/L EGTA, and 0.4% bovine serum albumin (pH 7.4).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As one main downstream molecule of Akt, GSK-3 plays an important role in liver ischemia/reperfusion injury. Inhibition of GSK-3 has been shown to ameliorate liver ischemia/reperfusion injury [40-42]. In this study, we found that silencing of AK139328 resulted in inhibition of GSK-3 in ischemia/reperfusion treated mouse livers, which is consistent with Akt activation.…”
Section: Discussionsupporting
confidence: 76%